Strategi Pembelajaran Berbasis Media Visual untuk Meningkatkan Pemahaman Anak Slow Learner di Desa Grujugan - Mishbahus Surur; Hawa Icha Sania Salma; Iislamiyah Iislamiyah; Dedy Aryasandi Utomo; Aufar Fadlul Hady (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Slow learners are students who experience slower learning processes compared to their peers and therefore require adaptive and contextual learning strategies. One effective approach is the use of visual media as a learning stimulus. This study aims to describe visual media-based learning strategies to improve the understanding of slow learner children in Grujugan Village. The research employed a qualitative method with a descriptive approach. The research subjects consisted of slow learner children, teachers, and parents selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation. The findings indicate that the use of visual media such as pictures, diagrams, and concrete teaching aids significantly improves students’ focus, participation, and conceptual understanding. Furthermore, the integration of visual media with repetition techniques and individualized instruction positively influences students’ motivation and self-confidence. Despite challenges such as limited learning resources and teachers’ time constraints, educators’ creativity and environmental support contribute to successful learning outcomes. This study concludes that visual media-based learning strategies are effective in enhancing slow learners’ understanding and are suitable for implementation in inclusive education, particularly in rural areas.